(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This report examines the impact of traffic congestion on quality of life in Saudi Arabia’s Eastern Province, a major industrial and economic hub that accounts for roughly 23% of the Kingdom’s industrial establishments and 22% of its GDP. It shows how rapid economic and population growth, combined with urban expansion and strong inter-city linkages between Dammam, Khobar, and Dhahran, have placed mounting pressure on road networks—worsening congestion and negatively affecting economic productivity, transport costs, traffic safety, and residents’ quality of life. The report reviews current policy responses (such as rapid bus transit, traffic-signal removal, and smart transport systems), and proposes medium- and long-term development policies including regional transit expansion, redistributing economic activity through secondary growth poles in Al-Ahsa and Jubail, and promoting hybrid work arrangements. It links these policies to Saudi Vision 2030’s goals of improving quality of life and building smart cities, concluding that traffic congestion is a structural regional phenomenon requiring functional regional reorganization rather than mere infrastructure expansion.